Taking Action in Elementary Science Teaching: A Reflection on Four Teachers’ Collaborative Research Journey - Kimberly Bilica (Networks: An Online Journal for Teacher Research, 2006)
In this paper, I will provide an example of how a team of four elementary and intermediate teachers of science made substantive changes in their classrooms based upon an action research study. First, I will discuss the connection between national science teaching standards and action research as a professional development. Next, I will describe how the teachers’ action research study, findings, and challenges. Last, I’ll describe the impact of the teachers’ activity on science teaching and learning, from a local and global perspective.